Fenomena Pernikahan Usia Dini di Tengah Transformasi Sosial: Studi tentang Implementasi Undang-Undang Nomor 16 Tahun 2019 oleh Kantor Urusan Agama Kecamatan Jombang - Yahuza, Wildan; Masrokhin, Masrokhin (Polyscopia, 2025)
This study investigates the effectiveness of the implementation of Law Number 16 of 2019, which sets the minimum legal age for marriage, in preventing early marriage in Jombang Subdistrict, East Java, while analyzing the role of the Office of Religious Affairs (KUA) as a key implementing institution at the local level. Although the law provides a more equitable and clearly defined age limit for both genders, field data reveal that marriages under the age of 19 persist, particularly in socioeconomically marginalized areas. Employing a qualitative descriptive approach, the research collected data through in-depth interviews, field observations, and internal documentation from KUA Jombang. The findings indicate that KUA has employed preventive strategies including legal education in schools, pre-marital counseling, and digital dissemination through social media. However, the continued use of court-issued marriage dispensations—often in response to premarital pregnancies or social pressure—remains a significant challenge. The study further emphasizes the influence of patriarchal cultural norms, economic hardship, and weak parental oversight in sustaining early marriage practices. Ultimately, KUA’s mediating role between state regulation and local values requires cross-sector collaboration and collective value transformation to ensure the law is internalized not only as legal doctrine but as a living social norm.